The Concept of Equality and the Rights of People with Disabilities under the Persons with Disabilities Act 2008 (Kanun: Jurnal Undang-undang Malaysia, 2023)
The Persons with Disabilities Act 2008, which came into force on July 7, 2008, shows the country’s commitment to helping people with disabilities (PWD).  The objective of this Act, which is to recognize the importance of accessibility to the physical, social, economic and cultural environment, to health and education and to information and communication, is to enable people with disabilities to fully and effectively participate in society.  The rights of people with disabilities cannot be seen in isolation with the human rights principles. Human rights, in a broader perspective, have become more important in today’s world.  This Act has succeeded in changing the concept of welfare to the concept of rights for people with disabilities in Malaysia.  Although this Act could be described as accommodating the rights of people with disabilities, it is still weak in terms of its enforcement, even though it was enacted 14 years ago. Thus, this article will examine and critically discuss the development of legislation on people with disabilities in Malaysia. This is due to the fact that the law is an important component of realizing the desire to see people with disabilities being treated fairly as those without disabilities. This concept of equality is not new because it is enshrined as a fundamental liberty that has been guaranteed by the Federal Constitution.Keywords: People with disabilities (PWD), welfare, legal, development, commitment, fundamental rightsFull text: PDF